2012
DOI: 10.1007/s11300-012-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Current Account Deficit: A Lesson from Pakistan

Abstract: This study investigates the determinants of current account deficit in Pakistan by using the annual time series data for the period 1976 to 2010. The cointegration results suggest the positive and significant long run relationship of current account deficit with exchange rate, trade deficit and fiscal deficit, while significant negative relationship is found with external debt and private saving. The error correction model also confirms the significant positive relationship of current account deficit with exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
(8 reference statements)
3
12
0
2
Order By: Relevance
“…Studies have been conducted to forecast the results of steady and unsteady exchange rates. Stability in exchange rates resulted in improved foreign investments, boost of exports and favourable change in balance of trade of the country (Berka & Devereux, 2010; Drine & Rault, 2006; Edwards, 1988; Khattak et al, 2012; Jawaid & Raza, 2013a). Unsteadiness in the trend of exchange rates enlarges the country’s trade deficit, increases inflation and cuts down the investment level (Eichengreen, 2008; Xiaopu, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted to forecast the results of steady and unsteady exchange rates. Stability in exchange rates resulted in improved foreign investments, boost of exports and favourable change in balance of trade of the country (Berka & Devereux, 2010; Drine & Rault, 2006; Edwards, 1988; Khattak et al, 2012; Jawaid & Raza, 2013a). Unsteadiness in the trend of exchange rates enlarges the country’s trade deficit, increases inflation and cuts down the investment level (Eichengreen, 2008; Xiaopu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, if the contribution of export is greater in a country’s trade openness, this will be reflected in the appreciation of the local currency. Likewise, the terms of trade can also contribute in the appreciation and depreciation of the home currency and also have an impact on the economic performance of a country (De Gregorio & Wolf, 1994; Diaz, 1982; Frenkel & Razin, 1992; Jawaid & Raza 2013b, 2015; Kumar, 2010; Roldos, 1990). Algieri (2011) suggested that for small open economy, enhancement in export prices augments terms of trade and boosts export revenues.…”
Section: Introductionmentioning
confidence: 99%
“…Murat et al (2014) found that the current account has weak sustainability in Turkey. Jawaid and Raza (2012) examine the determinants of the current account deficit in Pakistan by using annual time-series data for the period 1976–2010. The cointegration results suggest a positive and significant long-run relationship between the current account deficit and the variables considered, while a significant negative relationship is found with external debt and private saving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a plethora of country-specific and group-of-countries studies on the dynamics of the current account. For the latter category, see among others Murat, Hobikoglu and Dalyanci (2014) and Jawaid and Raza (2012) for Turkey; Matsubayashi (2005) for the United States; and Karunaratne (2010) for Australia, while in the case of the former, Huntington (2015), Edwards (2006), Milesi-Ferretti and Razin (1998), Kim, Min, Hwang and McDonald (2009) and Gnimassoun and Coulibaly (2014) are worthy of note. Observably, assessment of current account sustainability within the context of oil price variations has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The worsening position of the saving-investment ratio and foreign indebtedness are also considered as reasons of current account deficit. This study is an attempt to reinvestigate this issue for many reasons; first, scarcity of literature as we find only a few studies (Gulzar et al, 2007;Jawaid & Raza, 2013;Mukhtar & Khan, 2016) that have focused on this topic, second, absentees of consensus in their results as they have portrayed a mixture of results on this topic, and third, conducting research for the extended and latest time period. Figure 1 and Figure 2 are the graphical presentation of the current account deficit growth in the GDP of Pakistan.…”
Section: Introductionmentioning
confidence: 99%